Enzyme Stimuli-Responsive Nanoparticles for Bioinsecticides: An Emerging Approach for Uses in Crop Protection - Camara, Marcela Candido [UNESP] (2021)
The encapsulation of pesticides in systems responsive to enzymes allow for greater selectivity and specificity in pest control, in addition to contributing to reducing the impact on nontarget organisms and the environment. Therefore, the objective of this study was to investigate the synthesis of zein nanoparticles loaded with a mixture of botanical insecticides with release triggered by proteolytic enzymes found in the midguts of insects and larvae. The synthesis of the nanoparticles was carried out using the antisolvent precipitation method. Nanoformulations were characterized according to size, zeta potential, encapsulation efficiency, matrix and active ingredients interaction, and morphology. The enzymatic degradation was then studied. Nanoformulations have excellent encapsulation efficiency, greater than 95%, and stability over 60 days. The enzymatic tests showed significant reduction of the initial concentration of nanoparticles in 60 min and improved the release of geraniol, which increased from 15% to 56% in the presence of trypsin. Thus, the proteolytic enzymes were able to break down zein nanoparticles and stimulate the release of active ingredients providing a significant perspective for the control of crop insects.